2009
DOI: 10.1186/1471-2393-9-11
|View full text |Cite
|
Sign up to set email alerts
|

Elevated antiphospholipid antibody titers and adverse pregnancy outcomes: analysis of a population-based hospital dataset

Abstract: Background: The primary objective of this study was to determine if elevated antiphospholipid antibody titers were correlated with the presence of preeclampsia/eclampsia, systemic lupus erythematosus (SLE), placental insufficiency, and a prolonged length of stay (PLOS), in women who delivered throughout Florida, USA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 15 publications
1
36
1
4
Order By: Relevance
“…For decades, women particularly with SLE were advised against pregnancy given high rates of observed poor outcomes, concern for disease flare and lack of evidence for safe treatment options. Indeed, women with SLE/APS especially have higher rates of preeclampsia, intrauterine growth restriction (IUGR), and prematurity [24]. However, with advances in disease management, pregnancy outcomes in these populations have improved, and increasingly more women with CTDs are choosing to attempt pregnancies [5].…”
mentioning
confidence: 99%
“…For decades, women particularly with SLE were advised against pregnancy given high rates of observed poor outcomes, concern for disease flare and lack of evidence for safe treatment options. Indeed, women with SLE/APS especially have higher rates of preeclampsia, intrauterine growth restriction (IUGR), and prematurity [24]. However, with advances in disease management, pregnancy outcomes in these populations have improved, and increasingly more women with CTDs are choosing to attempt pregnancies [5].…”
mentioning
confidence: 99%
“…PE and intrauterine growth restriction (IUGR) -associated with impaired placentation -are obstetric complications frequently observed in APS (9)(10)(11)(12). Both conditions are major causes of maternal and fetal morbidity worldwide, with uncertain prevention and management (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…HELLP syndrome is defined as an endothelium-based disorder [61,62]. The increased prevalence of HELLP syndrome suggested by Ruffatti et al [69] 2006 Previous thromboembolism and/or triple antiphospholipid antibody positivity Sailer et al [39] 2006 Multiple antiphospholipid antibody positivity Danowski et al [45] 2009 Association with SLE or other SAD Nodler et al [53] 2009 High antiphospholipid antibody titres Ruffatti et al [70] 2009 Antiphospholipid antibody category I (Sydney criteria) or triple antiphospholipid antibody positivity…”
Section: Authors (Reference) Year Clinical Reports Treatment Protocolmentioning
confidence: 98%
“…More specific obstetrical manifestations include severe preeclampsia, which generally affects 2-8 % of pregnancies [52]. A cross-sectional study conducted in Florida on 141,286 women who delivered in 2001 showed that women with high antiphospholipid antibody titres had an increased risk of preeclampsia or eclampsia (adjusted odds ratio [AOR] = 2.93), placenta insufficiency (AOR = 4.58) and prolonged length of stay at hospital (>3 days, AOR = 3.93) [53]. Moreover, APS patients with history of cerebral ischemic events are at increased risk of preeclampsia (34.8 %), especially those positive for multiple antiphospholipid antibody test, and new cerebral ischemia can occur if preeclampsia develops (OR = 7.0) [42].…”
Section: Authors (Reference) Year Clinical Reports Treatment Protocolmentioning
confidence: 99%